Comparison of Three Related Concepts of Homonegativity among Three Faculties of Health Sciences - Moral de la Rubia, José (Consorcio de Universidades Mexicanas A.C., 2014)
The aims of this study were to: 1) define two components of (open/external and subtle/internal) rejection towards non-heterosexual persons; 2) calculate the means of rejection; 3) compare the means of rejection among three schools of health sciences and 4) controlling the effect of sex in these differences. The Attitudes towards Lesbians and Gay Men (ATLG) scale, the 16-item Internalized Homonegativity (IHN-16) scale and the 8-item Homophobia (HF-8) scale were applied to a non-probability sample of 231 participants (54 % women and 46 % men). One hundred students were surveyed in a public school of medicine, 66 in a private school of medicine and 65 in a public school of psychology. The two expected components were defined, one of open/external rejection and another of subtle/internal rejection. The means of the open/external rejection subscales and component corresponded to an answer of disagreement with the rejection. The means of the subtle/internal rejection subscales and component corresponded to an answer of ambiguity between rejection and acceptance. The means among the three schools were statistically differential in the subscales of subtle rejection towards homosexual men (ATG-S) and rejection towards public manifestation of homosexuality (EXT), and in the subtle/internal rejection component. The means of the rejection towards own homosexual fantasies, desires and identity (INT) subscale were differential among the three schools when sex was partialized. Effect sizes were small. It is concluded that the variable career had a significant effect on the rejection towards non-heterosexual persons. Acceptance was greater among psychology students than among medicine students.